Bureaucratisation And The State Revisited: Critical Reflections On Administrative Reforms In Post-renovation Vietnam - Benedikter, Simon (Penerbit Universiti Sains Malaysia (USM Press), 2016)
In spite of administrative reforms implemented over the past 30 years of Renovation Policy (Đổi mới) by the Vietnamese Communist Party with massive support from donor agencies, Vietnam's state machinery and bureaucracy has largely remained bloated and fragmented. As they evolved from state to market, administration and public service did not reform as envisaged in a long-term policy that aims to bring Vietnam closer to Western-dominated, normative models of "good governance." The ineffectiveness of these reforms has commonly been attributed to poor human capacity, weak law enforcement, inconsistent legal frameworks and similar types of formal institutional shortcomings, all of which ought to be remedied by strengthening formal institutions and capacity building. In going beyond such mainstream institutionalist views, this paper appraises administrative reforms from a more critical, sociological perspective. It takes into account socio-cultural and socio-political institutional factors, such as norms, values and worldviews, which often serve as pivotal elements shaping reform trajectories and outcomes. Conceptually, the paper draws on a 1987 study by Hans-Dieter Evers that traces different types of bureaucratisation as a means to unravel the nature of bureaucracy and its evolutionary process through the lens of social history. This study elucidates that despite formally proclaimed commitments to Weberian bureaucracy, in practice, bureaucratisation as currently observable in Vietnam is chiefly featured by strong tendencies of socalled Orwellisation and Parkinsonisation.